Molecular tag for promoting N-glycan maturation in the cargo receptor-mediated secretion pathway - Hirokazu Yagi; Rino Yamada; Taiki Saito; Rena Honda; Rio Nakano; Kengo Inutsuka; Seigo Tateo; Hideo Kusano; Kumiko Nishimura; Saeko Yanaka; Takuro Tojima; Akihiko Nakano; et al. (iScience)
Summary: MCFD2 and ERGIC-53 form a cargo receptor complex that plays a crucial role in transporting specific glycoproteins, including blood coagulation factor VIII, from the endoplasmic reticulum to the Golgi apparatus. We have demonstrated that MCFD2 recognizes a 10-amino-acid sequence in factor VIII, thereby facilitating its efficient transport. Moreover, the secretion of biopharmaceutical recombinant glycoproteins, such as erythropoietin, can be enhanced by tagging them with this sequence, which we have termed the “passport sequence” (PS). Here, we found that the PS promotes the galactosylation and sialylation of N-glycans on glycoproteins. Furthermore, we discovered that glycoproteins tagged with the PS follow a unique route in the Golgi, where they encounter NUCB1. NUCB1 also recognizes the PS and mediates its interaction with the galactosylation enzyme B4GALT1. These findings offer a promising strategy for controlling the glycosylation of recombinant glycoproteins of biopharmaceutical interest.